Gideon's corpse - Preston, Douglas J. (Preston, Douglas J. Gideon Crew novel., 2012)
A top nuclear scientist turns homicidal, taking an innocent family hostage at gunpoint. Gideon Crew, a colleague of the scientist at Los Alamos, is called in to talk the man down. But the standoff ends in an explosion of violence. When the authorities discover the scientist's body is intensely radioactive, and that he had recently embraced Islamic extremism, all hell breaks loose.